When does knowing better mean doing better? Trust in President Trump and in scientists moderates the relation between COVID-19 knowledge and social distancing. (31st May 2021) - Granados Samayoa, Javier A.; Ruisch, Benjamin C.; Moore, Courtney A.; Boggs, Shelby T.; Ladanyi, Jesse T.; Fazio, Russell H.
ABSTRACT: In response to the COVID-19 pandemic, scientists have sought to better understand the psychological characteristics associated with adoption of preventative behaviors. Several studies point to knowledge about the virus, trust in government officials, and trust in scientists as reliable predictors of social distancing, yet the exact nature of the relations between these predictor variables remains unexplored. Examining these relations in a study involving 998 participants, we found that less trust in former President Trump's ability to guide the nation through the COVID-19 crisis and greater trust in scientists predicted greater COVID-19 knowledge. In turn, greater COVID-19 knowledge predicted greater social-distancing behavior, and did so most strongly among those who reported (1) relatively low levels of trust in Trump and (2) relatively high levels of trust in scientists. These findings add a layer of complexity to our understanding of how knowledge about an issue and trust in authority figures shape behavior, suggesting that in addition to predicting the amount of knowledge people have on a certain issue, trust may play role in influencing the perceived validity of that knowledge as a basis for behavior. The implications of this work for campaigns aimed at increasing compliance with scientific guidelines are discussed.